Confronting cyber-bullying in schools: towards developing guidelines for cyber-bullying awareness in Highfields-Glenorah district secondary schools in Zimbabwe. - Chiwapu, Victor (Midlands State University, 2017)
This study considers the development of cyber-bullying awareness guidelines in three Highfeilds-Glenorah district secondary schools amongst the form twos, form fours and Advanced level students. The purpose of the study was to establish guidelines for cyberbullying awareness in form of a framework in Highfeilds-Glenorah district, and how the findings inform the district education officers, about the challenges faced by the schools in dealing with cyber-bulling. This study anticipated to help them to develop guidelines that might contribute towards the development of cyber-bulling awareness and in the process, contribute to a cyber-bulling free school environment. Critical research questions focused on three main areas: what are the schools doing to deal with cyber-bullying?, what do the learners think schools can do to stop cyber-bullying? and what do teachers think schools should do in order to curb cyber-bullying?, were answered. A review of the current literature was conducted; most of which related to secondary school aged pupils and from studies outside Zimbabwe. The literature had informed the research questions in terms of bringing them together to be asked in this research paper. The methodology used was the mixed method approach. The instruments used a combination of questionnaires, interviews and focus groups and data analysis to triangulate data collection and analysis, from both staff and students on the topic. The study sample size comprised of 105 students who responded to the questionnaire, 18 participants of three focus groups, three administrator interviews and two computer teacher interviews. The results indicate that cyber-bullying awareness does not exist in the schools. A number of recommendations were made which include a framework to deal with cyber-bullying in the schools. Opportunities for future research in this area are outlined.